Wear and microstructural properties of Ni-B4C/CNF composites - Islak Serkan; Koç Vahdettin; Gariba Abdualkarim Musbah M. (National Library of Serbia, 2022)
The aim of this study is to investigate the microstructure and wear properties of nickel (Ni) matrix boron carbide (B4C) and carbon nanofiber (CNF)-reinforced composite materials. Microstructure and phase composition of the composites manufactured by powder metallurgy (PM) method were determined by SEM-EDS and XRD analysis. While hardness values of the composites were determined by Vickers hardness measurement method, their wear properties were determined by using pin-on-disc method. SEM images showed that B4C was homogeneously distributed, but CNF accumulated in some areas, even though it was slight. Addition of B4C and CNF to the matrix significantly increased it. The increase was quite high in B4C addition, and hardness was slightly lower in the addition of CNF. According to the results of the wear test carried out under dry conditions, the reinforcement to the Ni matrix reduced the wear rate and friction coefficient.
Keywords: nickel; wear; Chemical technology; carbon nanofiber; boron carbide; TP1-1185; composites